The Relationship Between Covid-19 Fear and Covid-19 Phobia of Nursing Students - Alcan, Aliye Okgün; Dolgun, Eda; Giersbergen, Meryem Yavuz Van; Çankaya, Askeri; Aykut, Züleyha; Kaçmaz, Elif Deniz (Aydın Adnan Menderes Üniversitesi, 2024)
Objective: The relationship between fear and phobia of COVID-19 in nursing students was investigated. Method: It is descriptive and cross-sectional type. It was conducted with 396 nursing students studying in two different universities in the 2020-2021 academic year. Coronavirus Fear Scale and Coronavirus-19 Phobia Scale were used. The data were collected online. Results: The mean age of the students included in the study was 21.06±1.94 years. In this study, it was determined that the total average point of the Coronavirus Fear Scale of the nursing students was 16.47±6.26 (min:7 max:35) and the total average point of the Coronavirus 19 Phobia Scale was 44.92±16.90 (min:20 max:100). It was determined that there was a highly significant positive correlation between the total points of the Coronavirus Fear Scale and the Coronavirus-19 Phobia Scale total points of the nursing students (r:0.773 p:0.0001). Conclusion: It was determined that the mean point of COVID-19 Fear and the mean point of COVID-19 Phobia of the nursing students were moderate, and there was a relationship between the fear of coronavirus and the fear of coronavirus of the nursing students. It is recommended to determine the psychological needs of nursing students, to provide counseling regarding these needs, to be supported to increase their coping skills.

Amaç: Hemşirelik öğrencilerinde COVID-19 korkusu ile fobisi arasındaki ilişki incelenmiştir. Yöntem: Tanımlayıcı ve kesitsel niteliktedir. 2020-2021 akademik yılında iki farklı üniversitede öğrenim gören 396 hemşirelik öğrencisi ile yürütülmüştür. Koronavirüs Korku Ölçeği ve Koronavirüs-19 Fobi Ölçeği kullanılmıştır. Veriler internet üzerinden toplanmıştır. Bulgular: Çalışmaya alınan öğrencilerin yaş ortalaması 21.06±1.94 idi. Bu çalışmada hemşirelik öğrencilerinin Koronavirüs Korku Ölçeği toplam puan ortalamasının 16,47±6,26 (min:7 max:35) ve Koronavirüs 19 Fobi Ölçeği toplam puan ortalamasının 44,92±16,90 (min:20 max:100) olduğu belirlendi. Hemşirelik öğrencilerinin Koronavirüs Korku Ölçeği toplam puanları ile Koronavirüs-19 Fobi Ölçeği toplam puanları arasında pozitif yönde yüksek düzeyde anlamlı bir korelasyon olduğu belirlendi (r:0,773 p:0,0001). Sonuç: Hemşirelik öğrencilerinin COVID-19 Korku ve COVID-19 Fobi puan ortalamalarının orta düzeyde olduğu ve hemşirelik öğrencilerinin koronavirüs korkusu ile koronavirüs fobisi arasında ilişki olduğu belirlendi. Hemşirelik öğrencilerinin psikolojik ihtiyaçlarının belirlenmesi, bu ihtiyaçlara yönelik danışmanlık verilmesi, başa çıkma becerilerinin arttırılması için desteklenmesi önerilmektedir.
Hemşirelik Öğrencilerinde COVID-19 Korkusu ile COVID-19 Fobisi Arasındaki İlişkinin İncelenmesi
Keywords: Nursing (Other); Hemşirelik (Diğer)